Development of an approach to streamline process under competitive environment - Toh, Chin Seng. (2008)
The aim of this dissertation is to study the application of BPR and TQM to streamline operating processes for two companies in the face of intense competitive pressures. Real life application and examples are to be provided to illustrate the cases.